Stability Assessment of Cephradine Suspension Formulated in Bangladesh - Sultan, M. Z.; Mazid, M. A.; Rashid, M. A. (Journal of Scientific Research, 2011)
Cephradine, one of the commonly used and widely prescribed antibiotics in Bangladesh, is usually formulated in the dosage forms of capsule, dry suspension and IV injection. The dry-suspension is instructed to re-disperse in pre-boiled cooled water before use. A reversed phase high performance liquid chromatographic method (HPLC) has been developed for determination of cephradine in pharmaceutical preparation. To study the stability of cephradine suspension formulated by Bangladeshi manufacturers in aqueous medium and buffer of different pHs at room temperature, a simple and rapid chromatographic method was developed using acetonitrile and monobasic sodium phosphate buffer as mobile phase in the ratio of 15:85 (v/v) over C-8 bonded silica at ambient temperature using a flow rate of 1.0 mL/min. The study revealed that the potency of cephradine suspension was almost stable at room temperature up to 13 days in aqueous medium at pH between 4 and 5. Keywords: Cephradine; Suspension; HPLC; Potency; pH. © 2011 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved. doi:10.3329/jsr.v3i2.7024 J. Sci. Res. 3 (2), 383-391 (2011)